Breed Description of Experimental Horro Cattle at the Bako Agricultural Research Centre (17–19 May 2002) - Workneh, A.; Markos, T. (2002)
A brief breed survey was undertaken on 40 (30 female and 10 male) mature experimental Horro cattle at the Bako Agricultural Research Centre between 17 and 19 May 2002. The animals were brought in from Horro Gudru district of East Wollega, specifically Sekela, Hareto and Jerrie markets. Breed descriptors such as form and appearance, linear body measurements, body weight and images of adult animals were recorded. Live weights for adult breeding males and non-lactating breeding females without pregnancy or at their early pregnancy were 321 kg and 247, respectively. Males were 117 cm high at withers, compared to 113 cm for females. The body length was 114 cm for males and 103 cm for females. Coat colour is predominantly brown or red in plain pattern (90%). Only 10% of the animals, all of which were males, had pied coat colour pattern, where the head and shoulders took darker variation of the coat colour, in much the same way as the Boran bulls. Body linear measurements were also compared with other indigenous cattle breeds such as Ethiopian Boran and Sheko. The on-going experiment on genetic improvement of the Horro for dairy performance through crossbreeding with exotic breeds does not reflect the prevailing uses of the breed for traction, milk and then beef. Based on this, recommendations were forwarded and a remark was also made to the opportunity and challenge of the Centre as the only Horro cattle improvement programme to date.